Analisis Efektivitas Penerapan Layanan Publik E-Kelurahan di Kota Bandung - Cici Nurnovianti; Nia Karniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article analyses the effectiveness of E-Kelurahan public service implementation in Bandung City, which is part of the e-government initiative to improve the quality of public services through information technology. The research uses a qualitative and descriptive analytical approach to evaluate the successes, constraints, and areas of improvement in the implementation of the system. The results show that E-Kelurahan has improved service speed and transparency, although there are still challenges related to infrastructure, digital literacy, and human resource readiness. This research suggests the need for continued efforts in improving technological infrastructure and training for village officials to optimise public services.